TOLERANSI NASARUDDIN UMAR SEBAGAI SOLUSI MENANGGULANGI RADIKALISME ATAS NAMA AGAMA - Farkhan Fuady; Imanatur Rofiah; Selvia Ningsih (Academica: Journal of Multidisciplinary Studies, 2021)
Radicalism is synonymous with violence in carrying out its actions. Even today the radicalism movement in the name of religion as a vehicle to achieve their goals. There needs to be an effort to tackle radicalism in Indonesia. The effort is to instill religious tolerance. This study aims to examine the concept of tolerance according to Nasaruddin Umar. That in instilling a tolerant attitude is expected to be able to overcome radicalism. This study uses a qualitative method, with a literature review approach. Books, scientific articles, and other sources that are believed to be sources of research data. This study found that tolerance according to Nasaruddin Umar is respecting and respecting the rights of others. In implementing tolerance, he is committed to tackling radicalism in Indonesia. Several efforts were made to establish the Nasaruddin Umar Office and to promote the importance of tolerance in society through social media.Keywords: Nasaruddin Umar; radicalism; tolerance